Morphological study within some Algerian populations of Trifolium bocconei Savi - Issolah R.; Abdelguerfi A. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
In the framework of the evaluation and valorization of plant genetic resources of fodder and pastoral interest in Algeria, three Algerian populations of the species Trifolium bocconei Savi have been the subject of a morphological study of fruiting heads, pods and seeds. Ten characters were considered. The data of the natural habitat of the populations (rainfall, altitude, longitude, latitude) were also taken into consideration during the statistical treatments. The analysis of variance highlighted interesting results. A relationship seems to exist between the number of pods per fruiting heads and the latitude of the environment of origin of the populations. As a very rare clover in Algeria, Trifolium bocconei should be conserved and valorized, particularly in the marginal areas of the country.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)